Child Food Insecurity and Neighborhood Food Environment in Relation to Academic Performance and Behavior Problems Among a National Sample of Kindergarten Children (OR02-04-19) - Wang, Yan (Curr Dev Nutr, 2019)
OBJECTIVES: This study assessed food insecurity in relation to academic performance and behavior problems among kindergarten children from low-income families and the moderating effect of neighborhood food access (NFE). METHODS: Dataset of ECLS-K:2011, a nationally representative sample of kindergarten children attending elementary schools in 2010–2011 is linked to the 2010 Food Access Research Atlas based on census tract identifier. The analysis was restricted to 6460 children participating in the spring kindergarten assessment in families at or below 200% federal poverty level (FPL). Based on the USDA-validated Food Security Scale in the parent interview, food insecurity (FI) was defined as >3 affirmative responses to child-specific questions. Direct assessments of academic performance were administered; scaled scores were based on item response theory. Teachers reported internalizing/externalizing behavior problems with the Social Skills Rating System. Food desert was defined as a low-income census tract with at least 500 people and/or 33% of the population living >1 mile (urban) or >10 miles (rural) from the nearest supermarket. Survey regression analyses accounted for complex sampling design. RESULTS: 11.6% of low-income children were food insecure. 19% lived in food deserts. Children with FI had lower scores for reading (b = −1.23, SE = 0.59, P = 0.039) and math (b = −1.43, SE = 0.56, P = 0.011), than children without FI, with no moderating effect of NFE. No differences existed in behavior problems by FI status, accounting for demographic variables. NFE significantly moderated the relation between FI and externalizing behavior (b = 0.16, SE = 0.07, P = 0.033). Among children living in food deserts, those with FI had higher externalizing behaviors (b = 1.04, SE = 0.06, P = 0.024) than those without FI. FI was not related to externalizing behavior among children not living in food deserts. CONCLUSIONS: Child food insecurity among kindergartners is associated with low academic performance regardless of food access, and externalizing behaviors among children in food deserts. Efforts to reduce food insecurity among families of young children may promote academic performance, and strategies to incorporate healthy food into convenience stores in food deserts may prevent behavior problems. FUNDING SOURCES: NICHD.